Characterization of Clays from Adamawa State, Nigeria, for 3D Printing Applications - Abdulhameed U. Abubakar,; Ismail A. Yahya,; Emmanuel W. Gadzama,; Hijab A. Mahmoud,; Hassan M. Yusuf,; Shuaibu Abdullahi,; Aliyu Idris,; Mohammad B. Yawale,; Yazid Aliyu,; Masi L. Tumba,; Sabo Bala,; Ayuba T. Buni,; et al. (Journal of Advanced Industrial Technology and Application, 2025)
The Sustainable Development Goal 6 aims to ensure availability and management of sustainable water and sanitation, and this is particularly poignant for rural communities that rely heavily on sources such as streams, rivers, hand dug wells and in rare cases boreholes. In Nigeria, only a fraction of the population use improved drinking water sources and sanitation facilities. This makes access to safe and clean drinking-water in the rural areas of Nigeria practically impossible, leading to several health complications. This plays a significant role in diarrhoea related cases in Nigeria, in both adults and children. This research assessed the viability of locally sourced clay from Adamawa State as candidate material for 3D ceramic printed water filter. The assessment involves testing the physical, microstructural and mineralogical properties of the local materials obtained from different areas of the State. A prototype water filer was developed following geometric designs in Autodesk Fusion 360, and trial mix designs of composite materials using 3D printing extrusion process. The result indicates that the clays satisfied minimum plasticity requirements and exhibited satisfactory extrusion property. Heavy metals were not detected in all the clay materials, and composition displayed high amounts of silica and alumina content. The application of 3D printing technology will go a long way towards improving state-of-the-art and refinining the process as well as provide real time opportunity for correcting and editing flaws detected at each stage of prototype development as oppose to the traditional pottery process.